PENGUKURAN FREKUENSI NADA DASAR DAN WARNA BUNYI SARON SANGA LARAS SLENDRO GAMELAN JAWA MENGGUNAKAN PERANGKAT LUNAK SOUND FORGE - , ADRIANUS KUSUMA S, Dr. Mitrayana, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to measure the prominent frequency and timbre of gamelan, especially saron sanga laras slendro. Saron sanga is traditional musical instrument, created manually and tuned by experience of the creator. As a result, the tone of the saron sanga does not have standard frequency such as modern musical instruments. This research also see the correlation between the bar geometry of saron sanga to the prominent frequency. The result of this research is will be enriching the scientific understanding of the unique characteristics of Indonesian traditional musical instruments, especially saron sanga laras slendro. Research is executed in 2 (two) samples of different saron sanga at Balai Budaya Minomartani. Each saron sangaâs bar is struck at constant pressure. Concurrently, the sound is recorded by microphone that connects to a personal computer with Sound Forge 6.0 software. This software works based on Fast Fourier Transformâs algorithm to generate the sound frequency spectrum graph. From this graph, it can be computed the prominent frequency and the harmonic frequency that make up the timbre. Geometry measurement is conducted by measuring the length and thickness of the bar using a ruler. The results shows the average value of prominent frequency from nine saron sangaâs bars ( f0 Â± Îf0) is (468Â±1) Hz, (544Â±1) Hz, (621Â±1) Hz, (714Â±1) Hz, (819Â±1) Hz, (937Â±1) Hz, (1089Â±1) Hz, (1240Â±1) Hz, and (1427Â±1) Hz. The numbers of harmonic frequency and inharmonic frequency varies to each bar. The linearity equations that show the correlation of geometry measurements to the prominent frequency of both saron sanga are f0 = 2868 ôdL2ô+ 96 and f0 = 2655ôdL2ô+ 91.